The state accounting doctrine book of the Middle East in the 14th century: Risale-i Felekiyye and its place in accounting culture - (:unkn) unknown (ELSEVIER SCI LTD, 2015)
The advanced financial structure of the Ilkhanian State (1256-1353) is well known. The state accounting doctrine books that survive from this powerful state influenced public accounting and management practice in the Ottoman Empire and Middle Eastern region for hundreds of years. These accounting books were written in 1309-1363. The last and the most developed book in the series is 'Risale-i Felekiyye Kitab-us Siyakat'. The Risale-i Felekiyye-Kitab-us Siyakat contains accounting examples written in Siyakat script. The purpose of this paper is to demonstrate the functioning of financial orders and fiscal orders that facilitated decision making and the types and total of revenues and expenses of a state accounting system in 14th century. Thus, it describes a system of public accounting that facilitated financial planning and control, and a structure that integrated easily with fiscal management. Risale-i Felekiyye is seen as an excellent example of a written doctrine of accounting book with explanations of an accounting system and advanced level of accounting understanding. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Accounting; Stair (Merdiven) Method; State accounting system